PENGARUH RETURN ON ASET, RETURN ON EQUITY, DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR HOTEL, RESTORAN DAN PARIWISATA YANG TERDAFTAR DI BEI PERIODE 2015 – 2018 - Abet Setyoko; Setyaningsih Sri Utami; Dorothea Ririn Indriastuti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This research aims to analyze the significance of the effect of ROA, ROE and EPS simultaneously and partially on the stock prices of the hotel, restaurant and tourism sub-sectors listed on the Indonesia stock exchange in the 2015-2018 period. The population of this research are all companies in the hotel, restaurant and tourism sub-sector. The sampling technique uses purposive sampling of 10 companies. The type of data used is secondary data from www.idx.co.id. Data analysis techniques using multiple linear regression analysis, analysis results partially with the t test showed that the ROA and ROE variables did not have a significant effect on stock prices, while the EPS variable had a significant effect on stock prices. Simultaneous test results showed the variable ROA, ROE and EPS significantly influence stock prices. The coefficient of determination is shown from the adjusted R-square value of 0.014. This means that 14% of the share price is influenced by ROA, ROE and EPS, while the remaining 86% is explained by other variables not examined in this research.